Efficiency enhancement in energy production of photovoltaic modules through green roof installation under tropical climates - Arenandan V.; Wong J.K.; Ahmed A.N.; Chow M.F. (Ain Shams University, 2023)
Roofs; Solar power generation; Tropics; Building rooftop; Efficiency enhancement; Energy productions; Green roof; Performance; Photovoltaic modules; PV module temperature; PV system; Solar photovoltaics; Tropical climates; Solar cells